2015
DOI: 10.1111/ipd.12215
|View full text |Cite
|
Sign up to set email alerts
|

A study on the survival of primary molars with intact and with defective restorations

Abstract: Survival rates for primary molars with intact and defective amalgam and ART restorations were high. The 3-year survival rate of primary molars with intact restorations was significantly higher than that of primary molars with defective restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Nevertheless, due to the relatively short lifespan of primary teeth, the decision for re‐intervention in a defective restoration is not always an easy task. A previous study compared the survival rates of primary molars with intact and defective restorations . The survival rate of primary molars with intact restorations was higher (96.3%) than primary molars with defective restorations (75.9%) over a 3‐year period.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Nevertheless, due to the relatively short lifespan of primary teeth, the decision for re‐intervention in a defective restoration is not always an easy task. A previous study compared the survival rates of primary molars with intact and defective restorations . The survival rate of primary molars with intact restorations was higher (96.3%) than primary molars with defective restorations (75.9%) over a 3‐year period.…”
Section: Discussionmentioning
confidence: 97%
“…The survival rate of primary molars with intact restorations was higher (96.3%) than primary molars with defective restorations (75.9%) over a 3‐year period. Based on results, it was suggested that the recommendation to replace or to repair a defective restoration in primary teeth should consider several factors such as type of failure, age (related to tooth exfoliation), oral hygiene standards, and access to fluoride sources of the patients . Previous studies have already shown the detrimental effects of poor oral hygiene and high caries‐risk children on restoration survival of primary teeth …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations